Heritage book from Mircea Filip collection (Confluenţe Bibliologice, 2017)
Mircea Filip collection were integrated in the Scientific Library in 2016. It contains patrimony of great importance. The author invites readers to an exciting journey into the world of books, gathered in a life of Man, to discover together their charm and wisdom, the spirit of the characters created in different time spaces. True biblical values have today become the books on which the dedication or Ex-Libris of the author is preserved.
Keywords: Rare Book Collection; private collection